Influência do hidroperíodo no banco de propágulos dormentes de invertebrados aquáticos em áreas úmidas de altitude no Sul do Brasil - Wüsth, Regiane (Universidade do Vale do Rio dos Sinos, 2014)
The wetlands are among the ecosystems that contribute the most to biological diversity. On the other hand, are also considered the most threatened ecosystems by human action. The intermittent wetlands are defined by its hydroperiod, characterized by the number of months in which those present surface water during a year. The hydroperiod is an important factor to invertebrate communities in wetland systems, directly affecting the species that need to complete part or all of their life cycle in the water. In intermittent wetlands, species of aquatic invertebrates produce dormant propagules able to resist desiccation, constituting a fundamental evolutionary and ecological reserve in response to adverse conditions related to fluctuations in the hydrological regime and other environmental factors. The main objective of this study was to analyze the emergence of aquatic invertebrates via banks of dormant propagules in dry sediment of intermittent wetlands located in high altitudes in southern Brazil, relating the responses of the community with different hydroperiods. The specific objectives are: 1) Compare the richness, abundance and composition of drought-resistant aquatic invertebrates between wetlands that have different hydroperiods, and 2) Identify taxa of drought-resistant aquatic invertebrates which may be used as indicators of different hydroperiods in wetlands in southern Brazil. Sediment samplings were carried out in nine intermittent wetlands distributed in three treatments of hydroperiod (short, medium and long) located in southern Brazil, within the Atlantic forest biome. In the laboratory, the dry sediment was hydrated with distilled water and kept under controlled temperature and photoperiod. The invertebrates were sampled on the first day after hydration, and weekly for 10 weeks. A total of 19,868 individuals distributed in 11 taxa were found throughout the experiment. The richness, abundance and composition of aquatic invertebrates did not vary between the different hydroperiods. However, Karualona muelleri was more abundant in wetlands with short and medium hydroperiods and Kurzia polyspina, on the other hand, was most abundant in wetlands with long hydroperiod. The tardigrades were abundant in wetlands with medium hydroperiod. Our study showed that the studied wetlands can be easily recolonized after a dry period and that the drought-resistant aquatic invertebrate communities play a critical role in the ecological succession in southern Brazil wetlands.
Keywords: Altitude; Invertebrados; Dormência; Hidroperíodo; Intermitência; Altitude; Invertebrate; Dormancy; Hydroperiod; Intermittent; ACCNPQ::Ciências Biológicas::Biologia Geral